From Blended Learning to Online Learning: A Java Programming course case study. - Jupit, Amelia Jati Robert; Tan, Ping Ping (Universiti Malaysia Kelantan, 2020)
The innovation that had been conducted for our Java programming course is a mixture of asynchronous interactive online learning: H5P interactive videos, interactive lesson, online discussions and an-hour face-to-face online lecture. To ensure students’ understanding, questions are placed at different points in our H5P interactive videos, creating interaction while listening to the lectures. The interactive lesson provided students a step-by-step guide to programming. This lesson was designed to be followed by questions to ensure that the students have explored the steps. Online discussions were created every week so that students are aware that their lecturers are there for them.